Lazy Merging: From a Potential of Universes to a Universe of Potentials - Schürmann, Jonas; Steffen, Bernhard (Electronic Communications of the EASST, 2023)
Current collaboration workflows force participants to resolve conflicts eagerly, despite having insufficient knowledge and not being aware of their collaborators’ intentions. This is a major reason for bad decisions because it can disregard opinions within the team and cover up disagreements. In our concept of lazy merging we propose to aggregate conflicts as variant potentials. Variant potentials preserve concurrent changes and present the different options to the participants. They can be further merged and edited without restrictions and behave robustly even in complex collaboration scenarios. We use lattice theory to prove important properties and show the correctness and robustness of the collaboration protocol. With lazy merging, conflicts can be resolved deliberately, when all opinions within the team were explored and discussed. This facilitates alignment among team members and prepares them to arrive at the best possible decision that considers the knowledge of the whole team.